Academic Motherhood : How Faculty Manage Work and Family. - Ward, Kelly (Kelly Anne) (Rutgers University Press, 2012)
Academic Motherhood tells the story of one hundred women who are both professors and mothers and how they navigated their professional lives at different career stages. It is based on a longitudinal study that asks how women faculty on the tenure track manage work and family in their early careers when their children are under the age of five, and again in mid-career when their children are older. Policy recommendations that support faculty with children and mechanisms for problem-solving at personal, departmental, institutional, and national levels are provided.